An efficient method for fetal electrocardiogram extraction from the abdominal electrocardiogram signal - Hasan, Muhammad Asfarul; Ibrahimy, Muhammad Ibn; Reaz, Mamun Ibn (Science Publications, 2009)
Problem statement: FECG (Fetal Electrocardiogram) signal contains potentially precise information that could assist clinicians in making more appropriate and timely decisions during pregnancy and labor.